Применение математических преобразований для определения профиля медицинского электронного пучка - Банщикова М. А. Маргарита Александровна; Булавская А. А. Ангелина Александровна; Григорьева А. А. Анна Анатольевна; Стучебров С. Г. Сергей Геннадьевич (2023, 2023)
Текстовый файл